FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP WILAYAH JAKARTA UTARA - JULIANI JULIANI; RIAN SUMARTA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to obtain empirical evidence of understanding of taxpayers, taxpayer awareness, taxes sanction, taxpayer environment, quality of service, moral obligations and perceived behavioral control of taxpayer compliance. The use of the method in this study is causality research method. The population in this study is an individual taxpayer that registered in North Jakarta Tax Office. Sampling in this study used a simple random sampling method with a total of 103 respondents. The results of this study concluded that understanding of taxpayers, taxes sanction and moral obligations has an influence on the compliance of individual taxpayers registered in the North Jakarta Tax Office. In the sense that the higher the level of understanding of the taxpayer, the firmer the tax sanctions and the better the moral obligations, the higher the level of compliance of individual taxpayers. While taxpayer awareness, taxpayer environment, quality of service and perceived behavioral control do not affect the compliance of individual taxpayers registered in North Jakarta Tax Office.